Oral manifestations of Japanese patients with osteogenesis imperfecta. Issue 2 (August 2017) - Okawa, Rena; Kubota, Takuo; Kitaoka, Taichi; Kokomoto, Kazuma; Ozono, Keiichi; Nakano, Kazuhiko
Abstract: Objective: Osteogenesis imperfecta is a rare inherited skeletal disease known to be associated with oral problems. In the present study, we investigated the oral condition of Japanese patients with osteogenesis imperfecta using a nationwide survey. Subject and methods: A total of 534 clinics were surveyed by questionnaire, including 69 clinics registered to train paediatric dentists and 465 registered to train oral surgeons, to determine the number of osteogenesis imperfecta cases and the clinical dental findings of each case. Cases in the authors' clinic were also investigated. Results: Dentinogenesis imperfecta was found in 64% of the total 110 cases of osteogenesis imperfecta, most commonly in type III and IV osteogenesis imperfecta. The most common malocclusion was mandibular protrusion or anterior cross-bite, followed by open bite. Approximately 40% of all patients with osteogenesis imperfecta taking bisphosphonates underwent primary tooth extraction because of eruption disturbances with no complications. Conclusions: The main oral problem associated with osteogenesis imperfecta is dentinogenesis imperfecta. Treatment with bisphosphonates does not need to be interrupted when ectopically placed primary teeth are extracted to allow replacement by permanent successors. Periodic oral health management is recommended for patients with osteogenesis imperfecta, especially those with dentinogenesis imperfecta.